Pediatric Deciduous Molar Full Coverage Restorations: A Comparative Study of Stainless-Steel, Zirconia, and Fibreglass Crowns - Doaa Hemeda Elsayed ; Mohamed Sherif Salah Eldin ; Shaimaa Mohamed Mahfouz Omer (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Dental caries is a common condition that needs to be treated; the desire for durable and esthetic restorations in primary teeth continues to grow.  This study aimed to assess the clinical performance and the gingival health status of stainless Steel (SSCs), zirconia (ZRC), and fiberglass crowns (FIGC) in children. Patients and Methods: This a randomized controlled clinical trial on 44 children aged from 4 to 8 years old with mean age ±5.85. The selected children were divided randomly into two main groups, each group was subdivided into two subgroups according to the type of restorative crowns for primary molars. A total of 88 crowns were placed in 44 children who had 88 bilateral mandibular primary molars. Results: The highest scores for resistance to dislodgement before cement were recorded for SSCs followed by FIGC then the ZRC was the lowest one with statistically highly significant differences between the three treated groups of crowns. The highest scores for retention after cementation were recorded for SSC as it has a snap-fit and ZRC which have micromechanical locks present on the cementing surface within crowns that increases the surface area for cementation despite the greater tooth reduction while FIGC was the lowest group which showed complete loss of 10 crowns at the end of evaluation this seemed to be related to occlusal wear. The better gingival health was recorded for ZRCs followed by SSCs while the worst one was FIGCs with statistically highly significant differences between the three types of crowns according to the Gingival index (GI) at different time intervals. Conclusion:  Stainless steel crowns are still the “Gold Standard” for posterior full coverage restorations in primary molars followed by zirconia and fiber-glass crowns